A theoretical study of a family of new quinoxaline derivatives - Pis Diez, Reinaldo (2006)
Hybrid density functional calculations are performed on a series of 21 new quinoxaline derivatives, which would likely exhibit important biological activities. Optimized geometries, harmonic vibrational frequencies, and 1H chemical shifts are reported and compared with experimental data when available. In addition, melting points of 75 derivatives are predicted resorting to the Quantitative Structure–Property Relationship (QSPR) Theory, doing the variable selection by means of the Replacement Method and using 875 theoretical descriptors obtained from Dragon 5 software. The best relationship found has seven descriptors with R = 0.8818 and Rl-10%-o = 0.7705.